Literary Toposes in the Contemporary Bulgarian Media: Empirical Data [In Bulgarian] - N. Kantareva-Baruh (University of Sofia, 2013)
This article traces the emergence of a literary topos in contemporary Bulgarian public periodicals. The empirical material collected is expected to be of use for teaching practices in schools at all levels - from secondary to higher ones. It is also a snapshot of the contemporary Bulgarian journalism and society.